Preparation and characterization of microencapsulated paraffin wax as PCM for thermal energy storage / Mahyar Silakhori - Mahyar, Silakhori (2012)
Microencapsulation of paraffin wax with Polyaniline (PAn) Shell was synthesized as thermal energy storage materials by in-situ polymerization method. In this preparation, Paraffin wax was acted as the core material and PAn has been used as the shell which is environmentally friendly material. The chemical structure, surface morphologies, thermal properties and thermal stability of the encapsulated paraffin wax have been determined by Fourier transform infrared spectrophotometer (FTIR), Field Emission Scanning Electron Microscopy (FESEM), Differential Scanning Calorimeter (DSC), thermogravimetry analyzer (TGA), respectively. The FESEM results indicated that the paraffin wax was encapsulated well and the shape of the capsules are sphere .The DSC analysis showed that encapsulated paraffin wax has large energy storage and release capacity (22-140J/g) depending on the different ratio of the paraffin wax and PAn.TGA results indicated that the PAn can improve the thermal stability of encapsulated paraffin wax because of the synergetic effect between Paraffin wax and PAn. On the basis of all these results, the microencapsulated paraffin wax as MEPCMs has a good potential for thermal energy storage purpose.